Role of diet and gut microbiota on colorectal cancer immunomodulation - De Almeida, Carolina Vieira (World J Gastroenterol, 2019)
Colorectal cancer (CRC) is one of the most commonly diagnosed cancers, and it is characterized by genetic and epigenetic alterations, as well as by inflammatory cell infiltration among malignant and stromal cells. However, this dynamic infiltration can be influenced by the microenvironment to promote tumor proliferation, survival and metastasis or cancer inhibition. In particular, the cancer microenvironment metabolites can regulate the inflammatory cells to induce a chronic inflammatory response that can be a predisposing condition for CRC retention. In addition, some nutritional components might contribute to a chronic inflammatory condition by regulating various immune and inflammatory pathways. Besides that, diet strongly modulates the gut microbiota composition, which has a key role in maintaining gut homeostasis and is associated with the modulation of host inflammatory and immune responses. Therefore, diet has a fundamental role in CRC initiation, progression and prevention. In particular, functional foods such as probiotics, prebiotics and symbiotics can have a potentially positive effect on health beyond basic nutrition and have anti-inflammatory effects. In this review, we discuss the influence of diet on gut microbiota composition, focusing on its role on gut inflammation and immunity. Finally, we describe the potential benefits of using probiotics and prebiotics to modulate the host inflammatory response, as well as its application in CRC prevention and treatment.